Environmental influences on chorusing patterns in an Australian tropical savanna frog community - Sheryn Brodie; Slade Allen‐Ankins; Lin Schwarzkopf (Ecosphere)
Abstract Ecoacoustic methods provide opportunities for ecological studies of vocalizing species within the context of the natural habitats and communities in which they occur. Continuous acoustic monitoring of species assemblages can reveal patterns in breeding phenology, behavior, and interactions. We used long‐duration false‐color spectrograms derived from acoustic indices to detect the nightly chorusing of a community of anurans in a tropical savanna in north Queensland. We described the chorusing patterns of each species over two wet seasons at three breeding sites, and used conditional random forest analysis to investigate the influence of various environmental factors. Frogs in these habitats form multispecies aggregations at water bodies during breeding periods when males form large choruses to attract females. The chorusing patterns revealed the species have different breeding periods, which could be broadly categorized as explosive or prolonged. While rain events were often a trigger for the commencement of the breeding period, species responded differently to environmental conditions. Choruses of explosive breeding species occurred only on the night of, or night after, the first high rainfall event of the wet season. The prolonged breeding species showed idiosyncratic patterns of chorusing, which were generally consistent across sites. Fine‐grained nightly data on patterns of chorusing and the relationship with environmental conditions allow us to understand the detectability of the presence, or absence, of the frog species in these habitats, and provide baseline data for monitoring and management programs.